Mapping the Field: A Bibliometric Literature Review of Language Attitudes in Sociolinguistic Studies: Pemetaan Bidang: Tinjauan Literatur Bibliometrik tentang Sikap Bahasa dalam Kajian Sosiolinguistik - Angela Carolina Flores Riquelme (Universitas Tidar, 2025)
This bibliometric study systematically maps the intellectual structure and evolution of language attitudes research within sociolinguistics using Scopus and Web of Science databases from 2005-2024, employing VOSviewer and Bibliometrix R-package for network analysis, citation mapping, and thematic clustering to reveal significant disciplinary transformation from early sociopsychological frameworks toward critical, intersectional perspectives emphasizing language ideologies, identity construction, and social justice. The analysis demonstrates explosive research growth after 2015, with translanguaging studies achieving exceptional academic impact, particularly Fang and Liu's (2020) research on Chinese university contexts (151 citations, FWCI 15.00), while European institutions, led by Spanish universities, dominate heritage language education research and Asian contexts generate breakthrough empirical studies on multilingual identity construction. Keyword co-occurrence analysis identifies